TO WHAT EXTENT DOES THE SYLLABUS ALLOW TEACHERS TO GO BEYOND METHODS? - Rachmatika, Dian (Jurnal Bahasa Inggris, 2019)
?What is the best method to teach a foreign language?? Such queries might once come up in the minds of language teachers worldwide. While the answer to that question, if any, seems to be problematic, researchers in the area of language teaching argue that ?no size fits all? (see Kumaravadivelu, 2006), implying that there is no method apt to all characteristics of language classrooms. It then triggers an issue on teachers? dissatisfaction with the existing methods and underlies the emergence of post-method ideology. With the parameter of particularity, practicality, and possibility as well as the ten macro strategies, post-method pedagogy offers a breakthrough in language teaching. Not only does it promote teachers? autonomy to go beyond methods, but it also mitigates marginalization, neoliberalism, and dichotomy between theorists and teaching practitioners. Despite its benefits, in such contexts as Indonesia, the English as a Foreign Language (EFL) teaching framework is not generated under the umbrella of post-method principles. There might be a possibility for teachers, nevertheless, to go beyond methods and deploy the post-method pedagogy in their teaching. Such possibility is featured in the syllabus and thus becomes the objective of this study to critically review the extents to which the Indonesian EFL syllabus allows teachers to apply the post-method principles. By reflecting to the parameter and the framework of post-method, it can be deduced that the syllabus offers flexibility to some extent while several aspects need to be taken into account.